PEMBUATAN BIOETANOL BERBAHAN BAKU KULIT SINGKONG DAN KULIT NANAS DENGAN VARIASI MASSA RAGI - Rachmat Subagyo; Imam Ahdi Saga (Scientific Journal of Mechanical Engineering Kinematika, 2019)
This study aims to determine the best bioethanol levels from a combination of cassava and pineapple peels mixture with variations of yeast mass as much as 11 grams, 13 grams, 15 grams and 72 hours fermentation time, to determine the optimal yeast mass and determine ethanol levels according to SNI. This research was carried out by hydrolysis using distilled water for 30 minutes, then fermentation using yeast and distillation process, then tested with a Refractometer Pen. Selected samples will be tested for ethanol content using the Gas Chromatography tool. The highest ethanol content of ethanol making with a combination of cassava and pineapple peels is for a combination of 75% cassava peel - 25% pineapple peel 88.6% in a 15 gram yeast mass, a combination of 50% cassava peel - 50% pineapple peel 89.3% in 15 gram yeast mass. So it can be concluded that the ethanol content of the combination of cassava and pineapple peels is not included in the category of Indonesian national standards (SNI).